2013
DOI: 10.1007/s00345-013-1110-7
|View full text |Cite
|
Sign up to set email alerts
|

Karnofsky Performance Status predicts overall survival, cancer-specific survival, and progression-free survival following radical cystectomy for urothelial carcinoma

Abstract: Our study suggests the use of KPS to have predictive capacity in terms of OS, CSS, and PFS. This information can be used to inform patients' survival expectations prior to proceeding with radical cystectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 12 publications
3
34
2
Order By: Relevance
“…However, multivariate analysis for the overall cohort revealed that absence of PLND was not an independent predictive factor for prognosis in combination with the pathological T stage and pathological N stage (hazard ratio 1.440; 95 % confidence interval 0.166-12.52; P = 0.741). Furthermore, the 5-year OS in this study was 62.7 %, which is compatible with other results [5,20]. Second, it is possible that different surgical skill among institutions might affect prognosis and the incidence of complications.…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…However, multivariate analysis for the overall cohort revealed that absence of PLND was not an independent predictive factor for prognosis in combination with the pathological T stage and pathological N stage (hazard ratio 1.440; 95 % confidence interval 0.166-12.52; P = 0.741). Furthermore, the 5-year OS in this study was 62.7 %, which is compatible with other results [5,20]. Second, it is possible that different surgical skill among institutions might affect prognosis and the incidence of complications.…”
Section: Discussionsupporting
confidence: 76%
“…They reported that the ACCI was associated with clinical outcome for patients undergoing RC. However, investigations of whether comorbidity indices can be used to predict survival of patients with BCa have produced inconsistent results [5]. In our study, neither the CCI nor the ACCI was associated with OS after RC.…”
Section: Discussioncontrasting
confidence: 70%
See 3 more Smart Citations